Tolkien´s Imagination in the Lyrics of Contemporary Blackmetal Groups - Pausch, Roman (Univerzita Pardubice, 2022)
This thesis deals with Tolkien´s imagination in lyrics of Tolkien black metal bands from English-speaking countries. Its main goal is to analyze those lyrics, find common elements and contrast their usage with Tolkien´s literary work. The first part of the paper defines this musical genre and describes Tolkien´s influence on the black metal scene. The second part consists of text analysis that contrasts the portrayal of evil and nature in both fictional universes.
Tolkienova imaginace v textech současných blackmetalových kapel
Keywords: J.R.R. Tolkien; Pán prstenů; Středozem; vliv; Black metal; Tolkien Black metal; boj dobra a zla; příroda; hudba; zasasení; moc; válka; zlo; dobro; J.R.R. Tolkien; Lord of the Rings; Middle-Earth; Influence; Black metal; Tolkien black metal; Battle of good and Evil; Nature; Music; Setting; Power; War; Evil; Good